Analisis Kesesuaian APAR Sebagai Sistem Proteksi Kebakaran Aktif Pada Suatu Bangunan Di Pabrik Susu - Diyah Ayu Sukamto Putri; Zayyan Ahmad Arrafi; Mareta Pristiwanti; Moch. Luqman Ashari (Pusat Riset dan Inovasi Nasional, 2023)
Fire Extinguisher is one part of an active fire protection system that is used as a first step to extinguish a fire before the fire gets bigger. This research was conducted to assess the use of fire extinguishers in the Main Office building which is a part of the dairy factory building where activities in the Main Office building use a lot of electrical and paper-powered equipment which has a risk of fire hazard. Assessment of the use of APAR is carried out using quantitative and qualitative methods based on Permenaker Number 4 of 1980 and NFPA 10:2022. The results showed that the use of APAR reached 89% of all existing regulations.